The Challenge of Treating the Severest Forms of Chronic Noninfectious Posterior and Panuveitis - Spartalis, Christoph; Stübiger, Nicole; Spitzer, Martin S.; Bartsch, Udo; Atiskova, Yevgeniya (Klinische Monatsblätter für Augenheilkunde, 2023)
Background Noninfectious posterior and panuveitis may exhibit a chronic relapsing clinical course and are challenging to treat. Most affected patients are continuously treated with systemic immunosuppressive therapy, which is potentially associated with significant adverse side effects.Methods A cohort of 18 patients presenting with severe noninfectious posterior or panuveitis were evaluated with respect to the clinical course of the disease, with particular focus on best-corrected visual acuity (BCVA), treatment duration, remission rates, reported negative side effects, and the necessity for switching medication.Results The mean follow-up was 27.8 months. Although BCVA improved significantly, complete or partial remission was observed in only 66.7% of patients. Of the patients, 72.2% underwent a change in medical treatment due to either adverse events or inefficacy of medication.Conclusion Despite new immunosuppressive therapies, effective treatment of severe noninfectious posterior and panuveitis remains a major challenge. We discuss the urgent need for novel treatment strategies in order to prevent systemic adverse effects, and to improve visual outcome and quality of life.
Keywords: noninfectious uveitis; birdshot chorioretinopathy; serpiginous choroiditis; Behçets syndrome; Vogt-Koyanagi-Harada syndrome